2018
DOI: 10.1177/2325967118755991
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar Collateral Ligament Reconstruction Versus Repair With Internal Bracing: Comparison of Cyclic Fatigue Mechanics

Abstract: Background:Ulnar collateral ligament (UCL) injuries have increased significantly in recent years, and reconstruction has become the preferred treatment for UCL injury over ligament repair. In a recent study, UCL repair with internal bracing demonstrated significantly greater resistance to gap formation in biomechanical tests, even at low cycles of valgus loading.Purpose/Hypothesis:The purpose of this study was to compare the fatigue and failure mechanics of traditional UCL reconstruction with UCL repair and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 29 publications
(62 reference statements)
0
87
0
2
Order By: Relevance
“… 10 , 11 , 12 , 13 Interest in augmenting grafts during ACL reconstruction stems from the biomechanical and clinical success of suture augmentation in non-knee-related procedures such as Brostrom repairs 17 and ulnar collateral ligament repairs in the elbow. 18 Promising outcomes have also been seen in conjunction with medial knee injuries 19 , 20 and ACL repairs. 21 , 22 Recently, Bachmaier et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 11 , 12 , 13 Interest in augmenting grafts during ACL reconstruction stems from the biomechanical and clinical success of suture augmentation in non-knee-related procedures such as Brostrom repairs 17 and ulnar collateral ligament repairs in the elbow. 18 Promising outcomes have also been seen in conjunction with medial knee injuries 19 , 20 and ACL repairs. 21 , 22 Recently, Bachmaier et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nonanatomic femoral and tibial tunnel placement will result in inappropriate graft behavior during knee ROM and produce suboptimal outcomes. Although suture augmentation/reinforcement of Brostrom repairs, 17 ulnar collateral ligament repairs in the elbow, 18 medial knee injuries, 19 , 20 and ACL reconstructions 23 have shown excellent biomechanical and/or clinical results, long-term clinical outcomes after ACL reconstruction are unknown. Another concern is potential overconstraint of the knee, which can occur if the FiberTape sutures are tensioned too tightly.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several biomechanical studies have evaluated valgus stability of an internal brace combined with UCRL or repair [34][35][36][37][38]. Most studies demonstrated augmentation with an internal brace providing stability similar to that of the docking technique or more resistance to the valgus load.…”
Section: Biomechanical Studiesmentioning
confidence: 99%
“…[2][3][4] UCL reconstruction with a palmaris longus graft, commonly known as Tommy John surgery, has become the preferred treatment modality over ligamentous repair since first reported by Jobe et al in 1986. 5,6 The goal of the reconstruction was to recreate the function of the AOL. 1,7 Since its introduction, the technique for UCL reconstruction has undergone various modifications, and the most commonly used are the docking technique and the modified Jobe technique.…”
mentioning
confidence: 99%
“…Biomechanically, this construct has demonstrated a significantly greater resistance to gap formation during valgus loading when compared with conventional UCL reconstruction. 6 We present an augmentation construct that incorporates a cross-linked suture tape into the palmaris longus tendon autograft for UCL reconstruction.…”
mentioning
confidence: 99%